2018
DOI: 10.1080/00325899.2018.1446706
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the microstructure on the subsurface and surface damage during lubricated rolling–sliding wear of sintered and sinterhardened 1.5%Mo–2%Cu–0.6%C steel: theoretical analysis and experimental investigation

Abstract: The influence of the microstructure on density on the resistance to subsurface and surface damage, during lubricated rolling-sliding wear of a 1.5%Mo-2%Cu-0.65%C sintered and sinterhardened steel, was investigated. The nucleation of subsurface contact fatigue cracks and the occurrence of surface plastic deformation due to surface stresses were studied through a theoretical analysis and confirmed through wear tests. The expected positive effect of density and sinterhardening was confirmed. Moreover, the resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Accelerated wear tests can generally be motivated as long as the deformation and wear mechanisms are reproduced. In this study, the applied load is larger than in practice, and although cracks are found to initiate and propagate at a different rate, they propagate in the same manner as in materials tested for high cycle rolling contact fatigue, with and without slip [22,[25][26][27].…”
Section: Methodsmentioning
confidence: 99%
“…Accelerated wear tests can generally be motivated as long as the deformation and wear mechanisms are reproduced. In this study, the applied load is larger than in practice, and although cracks are found to initiate and propagate at a different rate, they propagate in the same manner as in materials tested for high cycle rolling contact fatigue, with and without slip [22,[25][26][27].…”
Section: Methodsmentioning
confidence: 99%
“…The material properties for the steel twin disc system (counter-face disc that is used to apply a compressive contact load and slave disk that is subjected to a contact load) are obtained for the analyses of Hertzian contact pressures and stress. The research was made using the dimensions and properties of two contacting materials where the geometry and material properties are obtained from the literature [19,20] as reported in Table 1. Radius of curvature R, mm 20 20…”
Section: Materials Property and Studied Geometrymentioning
confidence: 99%
“…The mean Hertzian pressure p o applied to the cylindrical contact surface is determined using the relation given by [19,26], as follows:…”
Section: Theoretical Hertzian Stress Analysismentioning
confidence: 99%